Do Rainfall Deficits Predict U.S.-bound Migration from Rural Mexico? Evidence from the Mexican Census - Nawrotzki, Raphael J. (2012)
Environmental and climatic changes have shaped human mobility for thousands of years and research on the migration-environment connection has proliferated in the past several years. Even so, little work has focused on Latin America or on international movement. Given rural Mexico’s dependency on primary sector activities involving various natural resources, and the existence of well-established transnational migrant networks, we investigate the association between rainfall patterns and U.S.-bound migration from rural locales, a topic of increasing policy relevance. The New Economics of Labor Migration (NELM) theory provides background, positing that migration represents a household-level risk management strategy. We use data from the year 2000 Mexican census for rural localities and socioeconomic and state-level precipitation data provided by the Mexican National Institute for Statistics and Geography. Multilevel models assess the impact of rainfall change on household-level international out-migration while controlling for relevant sociodemographic and economic factors. A decrease in precipitation is significantly associated with U.S.-bound migration, but only for dry Mexican states. This finding suggests that programs and policies aimed at reducing Mexico-U.S. migration should seek to diminish the climate/weather vulnerability of rural Mexican households, for example by supporting sustainable irrigation systems and subsidizing drought-resistant crops.